2018
DOI: 10.1039/c7ay02974h
|View full text |Cite
|
Sign up to set email alerts
|

Paper based lateral flow immunoassay for the enumeration of Escherichia coli in urine

Abstract: In this experimental study, we developed lateral flow immunoassay strips for the detection of Escherichia coli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Studies have shown that the detection performance of colorimetric methods can be improved by inducing the aggregation of nanomaterials in order to enhance the detection resolution [119,149,156]. Similarly, in the EC and SERS methods, the detection performance can be improved by patterning nanomaterials with good electrical conductivity on the electrode surface [120,125,135,166,167]. In CL and fluorescence methods, the intensity of the detection signal can be amplified through the catalytic reaction of nanomaterials and the induced fluorescence quenching [132,[168][169][170], respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have shown that the detection performance of colorimetric methods can be improved by inducing the aggregation of nanomaterials in order to enhance the detection resolution [119,149,156]. Similarly, in the EC and SERS methods, the detection performance can be improved by patterning nanomaterials with good electrical conductivity on the electrode surface [120,125,135,166,167]. In CL and fluorescence methods, the intensity of the detection signal can be amplified through the catalytic reaction of nanomaterials and the induced fluorescence quenching [132,[168][169][170], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For normal healthy individuals, the bladder can remove these bacteria on its own. However, in some cases, the bacteria may remain in the urinary system and cause infection [124,125]. In fact, most urinary tract infections (UTI) are caused by Escherichia coli (E. coli) [126][127][128], which normally appears in the rectum.…”
Section: Bacteria and Cancer Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…With issues such as poor infrastructure and limited funding already leading to underutilization of central laboratories in these resource-poor settings (Elbireer et al, 2011 ; Nkengasong et al, 2018 ), there is a growing interest in developing point-of-care techniques to diagnose a variety of diseases. Devices, such as miniaturized bioelectronics and microfluidic tests like the lateral-flow immunoassay (LFA), have received much attention over recent years due to their ease-of-use, portability, and limited need for power (Li et al, 2015 ; Sharma et al, 2015 ; Gumustas et al, 2018 ; Wang et al, 2018 ). However, in comparison to the gold standard laboratory-based tests, these devices are still restricted by their limited sensitivity, indicating an increasing need for enhanced detection capabilities at the point-of-care.…”
Section: Introductionmentioning
confidence: 99%